Missing the benefit of metformin in acute myeloid leukemia: A problem of contrast? - Alice C Ceacareanu; George K Nimako; Zachary A. P. Wintrob (Wolters Kluwer Medknow Publications, 2017)
Objective: To evaluate whether metformin's cancer-related benefits reported in patients with solid tumors (ST) are also present in acute myeloid leukemia (AML) patients. Methods: Baseline demographic and clinical history for all diabetes mellitus patients newly diagnosed with AML or cancer of the breast, ovary, prostate, gastrointestinal tract, lung, or kidney at Roswell Park Cancer Institute in Buffalo, NY (January 2003-December 2010, n = 924) was collected. Overall survival (OS) and disease-free survival (DFS) were assessed by Kaplan-Meier (KM) analysis and Cox proportional hazards regression (hazard ratio [HR]). Findings: Baseline metformin use provided significant OS and DFS benefit in ST but not in AML (KM: PST-OS= 0.003; PST-DFS= 0.002; PAML-OS= 0.961; PAML-DFS= 0.943). AML median survival was slightly better with metformin use, but users derived no relapse benefit. In ST, metformin nonusers had shorter median survival, 57.7 versus 86 months, and poorer outcomes (HRST-OS= 1.33; PST-OS= 0.002; HRST-DFS= 1.32; PST-DFS= 0.002). These findings remained significant in age-adjusted models (HRST-OS= 1.21; PST-OS= 0.039; HRST-DFS= 1.23; PST-DFS= 0.02) but not fully adjusted models (HRST-OS= 0.96; PST-OS= 0.688; HRST-DFS= 1.0; PST-DFS= 0.94). Higher mortality was noted in AML patients taking insulin versus oral diabetes pharmacotherapy at baseline (HRAML-OS= 2.03; PAML-OS= 0.04). Conclusion: Lack of metformin benefit in AML could be due to advanced age at cancer diagnosis. Metformin substitution with insulin before computed tomography scans with contrast - a frequent AML assessment practice - may also explain the lack of subsequent benefit despite taking metformin at baseline. A temporary metformin substitution is recommended by the package insert due to a possible drug interaction with the contrast dye. Our data suggest that metformin substitution was permanent in many patients. Nonetheless, the observed benefit in other malignancies warrants further investigation of metformin use in AML.